The European Convention of Human Rights and Migration at Sea: Reading the “Jurisdictional Threshold” of the Convention Under the Law of the Sea Paradigm - Efthymios Papastavridis (German Law Journal, 2020)
In all the applications before the ECtHR concerning migration at sea, a preliminary, yet seminal, question is whether the applicants were within the jurisdiction of the respondent State, in terms of Article 1 of the European Convention on Human Rights (ECHR). This question becomes even more apposite in contemporary situations of remote interception or search and rescue operations. In addressing the matter of jurisdiction in such cases, the law of the sea becomes of significant importance. This Article argues that as the International Tribunal of the Law of the Sea (ITLOS) has often taken into account human rights considerations, similarly, the European Court of Human Rights should read into the term “jurisdiction” under Article 1 of ECHR law of the sea considerations. Far from resurrecting Banković and the strict “general international law” notion of jurisdiction under ECHR, this Article only intends to shed some light on when a State would be considered as exercising such “authority and control over persons” in the maritime domain. In so doing, this Article will focus only on the potential application of the ECHR to the most common practices of States vis-à-vis migration on the high seas, namely interception and rescue operations.